Farmers' interest in crowdfunding to finance climate change mitigation practices. (25th October 2021) - Kragt, Marit Ellen; Burton, Rob; Zahl-Thanem, Alexander; Otte, Pia Piroschka
Abstract: Agricultural activities and associated land use change are a major contributor to global anthropogenic greenhouse gas (GHG) emissions, making climate change mitigation in the agricultural sector all the more critical. However, farmers' willingness to adopt GHG abatement depends, to a large extent, on the financial implications of new practices. Climate change mitigation is unlikely to be adopted without external (financial, socio-cultural, or other) incentives. The research presented in this paper considers farmers' preferences for financing climate change mitigation practices through public crowdfunding. As a first study of its kind, we investigate farmers' attitudes towards climate change mitigation, knowledge of crowdfunding as a fundraising method, and interest in using public crowdfunding campaigns to finance on-farm mitigation practices. Based on a choice experiment survey with 443 Norwegian farmers, we show that knowledge about crowdfunding as an alternative finance method is generally low. Respondents who are interested in using crowdfunding prefer donation- or reward-based crowdfunding models that cover the full cost of mitigation over a loan-based model or campaigns that only fund a proportion of the costs. A financially secure farming business, previous exposure to crowdfunding, and a strong sense of responsibility to abate climate change are associated with higher farmers' interest in using crowdfunding. We find that farmers in Norway are hesitant to be publicly presented as recipients of crowdfunding, which suggests that crowdfunding is best set up as joint campaigns (e.g. with other farmers) that are run by intermediary organisations (rather than by individual farmers). Our findings highlight that, while opportunities to use crowdfunding as a fundraising method for agricultural climate change may be limited, properly designed campaigns can provide an effective instrument to engage certain groups of farmers in on-farm climate change mitigation. Highlights: Crowdfunding can be used to raise funds for agricultural climate change mitigation. There is currently no research on farmers' interest in crowdfunding. We conduct a choice experiment survey of Norwegian farmers. About 25% of farmers would be interested in crowdfunding to finance mitigation measures. Donation- or reward-based models, and campaigns that collaborate with other farmers are preferred.